SISTEM PENGENDALIAN ASAP ROKOK MULTIKANAL DENGAN MENGGUNAKAN PWM BERBASIS MIKROKONTROLER ATMEGA 8 - valentina ginting (Saintia Fisika, 2013)
Has been designed and realized a series of control and smoke detector in the room Smoke ControlSystems Using Multi-Channel PWM-Based Microcontroller Atmega 8. Skema is designed based onmicrocontroller Atmega 8 and using MQ 2 sensor as an input to detect smoke in the room. Sensor ishave a high level of sensitivity to the two gases are Hydrogen and Ethanol is considered torepresent the gases contained in smoke. When smoke is detected the sensor resistance will decline,and rise again if smoke is detected density decreases. Once smoke is detected smoke concentrationsmeasured values are displayed on the LCD and will drop proportional to the decline in cigarettesmoke also detected. Fan speed will be proportional to the pulse width high is already in theprogram in accordance with microcontroller smoke levels were detected in room. This system hasbeen tested and construction tool is only in the form of simulation.Keywords: Cigarette Smoke, MQ2 sensor, microcontroller, LCD, PWM